Dupilumab-induced osteomuscular syndrome in a child with atopic dermatitis. - Gonzalez Montealegre, C.A.; Lopez Zornosa, V.P.; Giraldo Parra, M.J. (European Journal of Pediatric Dermatology, 2026)
Atopic dermatitis (AD) is a chronic inflammatory skin disease that in some cases requires systemic treatment to achieve adequate disease control. Dupilumab is a fully human monoclonal antibody that blocks interleukin-4 (IL-4) and interleukin-13 (IL-13) signaling by acting as an antagonist of the interleukin-4 receptor alpha subunit (IL-4Rα). However, several adverse events have been reported, including musculoskeletal symptoms. We report a case of dupilumab-induced non-inflammatory arthralgia. A 13-year-old girl with moderate AD was treated with dupilumab. Four months after treatment initiation, she developed left knee pain and low back pain. She was treated with nonsteroidal anti-inflammatory drugs and physical therapy without clinical improvement. Imaging and laboratory investigations showed no abnormalities. Based on these findings, an osteomuscular syndrome secondary to dupilumab administration was suspected. The drug was discontinued, and clinical improvement was observed four months after treatment withdrawal.